MERDEKA CURRICULUM, PANCASILA STUDENT PROFILE IMPLEMENTATION, AND LIL ALAMIN GRATITUDE IN MADRASAH IBTIDAIYAH - Insani, Isya Mulia; Ariyanti, Iva; Ratnasari, Hanis (Four Son Scholarship, 2023)
The Merdeka curriculum is a form of Indonesia's hope to encourage innovation and creativity in the field of education. Consideration of applying this curriculum is one of them, as a ransom for the learning loss that occurred over the past two years. This study presents facts related to the application, implementation, and implementation of the Merdeka Curriculum by combining the profiles of Pancasila students and Lil Alamin students of Mercy in Madrasah Ibtidaiyah. Type of qualitative research with interview methods. Planning is done through training related to the entire device of the Merdeka Curriculum. Implementation of learning in accordance with the teaching modules and project modules that have been compiled at the time of planning presents difficulties in combining the dimensions of Pancasila students and Lil Alamin Charity students. This is due to the lack of workshops and socialization related to the profile of Lil Alamine Charity Student. Results or reports of the implementation of learning activities, measured in data-scale numerical form and description Implementation of the Merdeka Curriculum requires training, guidance, and monitoring on a regular basis, mainly in coordination between the Profile of Pancasila Students and Lil Alamin Charity Students in the preparation of teaching modules as well as project modules